Peran Konsiliator Dalam Penyelesaian Perselisihan Pemutusan Hubungan Kerja - Grahadi Purna Putra (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to find out how to resolve employment termination disputes through industrial relations conciliation by a conciliator. The method used in this research is normative legal research, which is legal research carried out by examining library materials or secondary data. Based on the research results, it was concluded that due to the failure of bipartite negotiations by the parties in dispute regarding the termination of employment relations, the parties could choose a settlement through conciliation or arbitration. If the dispute between the parties is regarding termination of employment relations, then the choice is settlement through conciliation carried out by a conciliator, because settlement through arbitration can only resolve disputes of interest, and disputes between workers/labor unions only within one company. When an agreement is reached to resolve a dispute over termination of employment through conciliation, a joint agreement is made which is signed by the parties witnessed by the conciliator and registered at the Industrial Relations Court at the District Court in the jurisdiction of the parties entering into the collective agreement to obtain a certificate of registration, but if If no agreement is reached on resolving the employment termination dispute through conciliation, the conciliator issues a written recommendation and if the parties agree to the written recommendation the conciliator assists the parties in making a collective agreement to then be registered at the Industrial Relations Court